Risk Assessment of Typhoon Disaster Chains in the Guangdong–Hong Kong–Macau Greater Bay Area, China - Wang, Yujie; Yin, Yizhou; Song, Lianchun (Frontiers in Earth Science, 2022)
The typhoon disaster chain is one of the leading climate risks in constructing the Guangdong-Hong Kong-Macau Greater Bay Area (GBA). In this study, the risks of the typhoon disaster chains including typhoon-induced gales, rainstorms and storm surges in the GBA, as well as the comprehensive risk of typhoon disaster, are investigated at county level by comprehensively analyzing the hazard, exposure and vulnerability. The results show that the high risk areas of typhoon-gale disaster chain are located in Zhuhai, Zhongshan, Foshan, Dongguan, central-southern Jiangmen, southern Shenzhen and parts of Huizhou. The high risk areas of typhoon-rainstorm disaster chain include Zhuhai, Zhongshan, Shenzhen, central-southern Foshan, northern Dongguan, central Jiangmen and central Huizhou. Regarding the typhoon-storm surge disaster chain, the areas with relatively higher risk are located in Zhuhai, eastern Zhongshan and the coastal areas of the Pearl River Estuary. In addition, the comprehensive risk of typhoon disaster is the highest in Zhuhai and Zhongshan, relatively high in Jiangmen and Shenzhen, and relatively low in Zhaoqing and Huizhou. At county level, the high value areas of comprehensive risk of typhoon disasters are mainly distributed in the Doumen, Xiangzhou and Jinwan Districts of Zhuhai City, Zhongshan City, the Futian and Nanshan Districts of Shenzhen City, and the Yuexiu and Nansha Districts of Guangzhou City. By verifying the spatial correlation between typhoon disaster risk indexes and actual losses, it is found that the comprehensive risk index of typhoon disaster constructed in this study can better reflect the actual losses. Overall, the findings of this study can provide a scientific basis for typhoon disaster prevention and mitigation in the GBA, and it can also serve as a reference for typhoon disaster risk research in other areas.